Extreme variations in star formation activity in the first galaxies. Issue Volume 15:Issue S341(2019) (November 2019) - Binggeli, Christian; Zackrisson, Erik; Ma, Xiangcheng; Inoue, Akio K.; Vikaeus, Anton; Hashimoto, Takuya; Mawatari, Ken; Shimizu, Ikkoh; Hopkins, Philip F.
Abstract: Recently, spectroscopic detections of O[III] 88 μm and Ly-α emission lines from the z ≍ 9.1 galaxy MACS1149-JD1 have been presented, and with these, some interesting properties of this galaxy were uncovered. One such property is that MACS1149-JD1 exhibits a significant Balmer break at around rest-frame 4000 Å, which may indicate that the galaxy has experienced large variations in star formation rate prior to z ∼ 9, with a rather long period of low star formation activity. While some simulations predict large variations in star formation activity in high-redshift galaxies, it is unclear whether the simulations can reproduce the kind of variations seen in MACS1149-JD1. Here, we utilize synthetic spectra of simulated galaxies from two simulation suites in order to study to what extent these can accurately reproduce the spectral features (specifically the Balmer break) observed in MACS1149-JD1. We show that while the simulations used in this study produce galaxies with varying star formation histories, galaxies such as MACS1149-JD1 would be very rare in the simulations. In principle, future observations with the James Webb Space Telescope may tell us if MACS1149-JD1 represents something rare, or if such galaxies are more common than predicted by current simulations.